Personal Branding Through Online Dating App Bumble - Nabilah, Farah Hanin; Rochmaniah, Ainur (Procedia of Social Sciences and Humanities, 2024)
In contemporary society, personal branding has become an important aspect of self-presentation, especially in digital media. This study explores the phenomenon of personal branding through the popular online dating app Bumble. Through a qualitative analysis of user profiles and interactions within such platforms, the study aims to understand how individuals strategically build and manage their personal image to attract other users. Qualitative descriptive research method through data collection by interviewing 6 Bumble user informants and observing user profiles, including selected bio and images, as well as their interactions with other users in the application.The theory used is personal branding by Peter, Personal branding McNally and Speak, and self-presentation by Goffman Montoya analysis was carried out qualitatively to identify patterns in personal branding strategies used by bumble users. The results showed that Bumble users engaged in a variety of personal branding strategies, such as selective self-disclosure, image curation, and the use of language designed to portray desirable characteristics and values. In addition, visual elements, such as profile photos and aesthetics, also play an important role in the formation of online self-image. Overall, this research contributes to our understanding of personal branding in the context of online dating, providing insight into the complex dynamics of self-presentation and impression management in the digital environment. The findings have implications for academics and practitioners interested in the intersection of Technology, identity, and interpersonal relationships.